Perkembangan dan Tantangan Pasar Modal Indonesia - Lisa Ara Ghea Sagala; Susanti Nurmalasari; Siti Zakiyyah Frialyani; Dedi Mulyadi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The world is now reimagining itself to a normal situation after the pandemic hit. Gradually, the world economy began to move to catch up with those who had been paralyzed due to the pandemic, including in Indonesia. The increase in the number of investors is certainly a positive signal for the development of the capital market in Indonesia. It is hoped that the investment world will become lively again and play a role in moving the wheels of the nation's economy. The capital market has a very large role for a country's economy because the capital market performs two functions, namely the economic function and the financial function. This writing uses the library research method, with library data collection as a data source. As a consequence of global and economic integration, capital market performance in national, regional and international economic performance is determined by economic growth rates such as inflation rates, interest rates, exchange rates and the size of other macro indicators. This is an important foundation for the future growth of the capital market because it will determine the extent of the growth rate of the capital market.can be regulated clearly based on the Red Cross Affairs Law.